Inhibition of myosin IIA–actin interaction prevents ischemia/reperfusion induced cardiomyocytes apoptosis through modulating PINK1/Parkin pathway and mitochondrial fission. (15th November 2018) - Li, Fang; Fan, Xiaoxue; Zhang, Yu; Zhang, Yuanyuan; Ma, Xiaonan; Kou, Junping; Yu, Boyang
Abstract: Background: Mitochondrial fission is the essential mechanisms of myocardial ischemia/reperfusion (MI/R)-induced cardiomyocytes apoptosis. Myosin II plays a key role in fission due to the recruitment and actomyosin constriction at the fission site in U2OS cells. However, the role of myosin IIA–actin interaction in regulating MI/R-induced cardiomyocytes mitochondrial fission and apoptosis remains to be fully elucidated. Methods and results: When cardiomyocytes are exposed to simulated I/R injury, the myosin IIA protein translocated from the juxtamembrane to the cytoplasm, interacted with actin filaments, formed stress fibers and generated contractile forces. Treatment with the myosin II inhibitor blebbistatin attenuated the myosin IIA–actin complex induced actomyosin contractility and prevented cardiomyocytes apoptosis as reflected by inhibition of cleaved caspase-3 expression, normalization of Bcl-2/Bax levels and decreased apoptotic cells. Meanwhile, blebbistatin inhibited the activation of PINK1/Parkin pathway and ameliorated mitochondrial fission as evidenced by improvement of mitochondrial morphology, inhibition of Drp1 phosphorylation at Ser616 and translocation. Furthermore, CRISPR/Cas9 knockout of myosin IIA blocked I/R-induced apoptosis, suppressed PINK1/Parkin pathway and reduced mitochondrial fission. Importantly, blebbistatin attenuated myocardial apoptosis, inhibited myosin IIA–actin interaction and PINK1/Parkin pathway, suppressed myocardial ultrastructure abnormalities and mitochondrial fission in a mouse MI/R injury model. Conclusions: Inhibition of actomyosin contractility induced by myosin IIA–actin interaction could impede myocardial apoptosis and MI/R injury via PINK1/Parkin pathway and mitochondrial fission modulation both in vitro and in vivo, which may be applicable for the development of therapies for cardiovascular diseases. Highlights: Nonmuscle myosin IIA–actin regulates MI/R-induced cardiomyocyte apoptosis. Nonmuscle myosin IIA–actin modulates MI/R-induced mitochondrial fission. Myosin IIA-related actomyosin contractility modulates PINK1/Parkin pathway. Inhibition of myosin IIA–actin interaction attenuates myocardial injury. Provide new insights on MI/R-induced myocardial apoptosis